Critical Analysis on the Ad hoc Tribunal of Yugoslavia - Rojas González, Luisa (Frónesis, 2022)
Through this study, a critical view of the ad hoc Tribunal of Yugoslavia is offered with tools of international criminal law, Human Rights and International Humanitarian Law. It is analyzed how the historical political fact of the separation from Yugoslavia generated crimes against humanity and for the prosecution of those responsible for these crimes, the UN Security Council created said Court, which was in operation until December 2017. Competition and jurisdiction are examined, as well as the characteristics of operation. As a review of action, two relevant cases were incorporated that culminated in convictions.